Pengaruh Kualitas Produk dan Citra Merek terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan pada Produk Kopi Siap Minum Luwak White Koffie di Kota Cimahi - Ramdan, Faiz Muhammad; Yun, Yun (Universitas Batanghari, 2024)
Businesses need to be more innovative and creative in how they run their operations due to growth and competition in all industries. To meet customer demand, the company takes various initiatives to increase sales of its products. The purchasing process begins when a person becomes aware of general needs and wants. The difference between the current and desired state begins to register in the individual's consciousness. Everyone has different perspectives and perceptions about the items they buy. Therefore, the way one person acts when buying something may be different from another person. By 2023, ready-to-drink coffee sales are expected to return to pre-pandemic levels. According to Euromonitor, Indonesia's coffee production will increase 7% from 2021/2022 and reach 11.35 million bags in 2022/2023. However, according to TBI 2023, sales of Luwak coffee have decreased since 2021. This has resulted in the problem of decreasing customer loyalty towards Luwak White Koffie ready-to-drink coffee products in the city of Cimahi. The instrument used in this research has been declared to have passed the validity test, reliability test, classical assumption test, multiple regression and sobel. This research will involve students in the city of Cimahi who have previously consumed Luwak White Koffie ready-to-drink coffee products. The data collection technique used is cross-sectional or one shot study